Fracture mechanics analysis of defence hole system for a uniaxially loaded plate using boundary element method - Lim, Chun Siang. (2010)
The effect on stress concentrate factor at the main hole by means of introducing defence hole on a uniaxially loaded plate was analysed using Boundary Elemrnt Method. It was noticed that introduction of defence hole systems to an uniaxially loaded plate will cause a reduction of stress concentration factor at the main hole and the reduction can be greater by increasing the diameter of the defence hole. The result obtained was compared with published paper and was found to be in good agreement..